Proceedings of the Conference on Recent Advances in Rock Engineering (RARE 2016) 2016
DOI: 10.2991/rare-16.2016.67
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Delay Detonators - Benefits a growth prospects in India

Abstract: Abstract-Since

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In recent years, with the popularization of electronic detonators initiation technology, more and more blasting projects have begun to use electronic detonators. The electronic detonators can be programmed to a delay increment of 1 ms or less which provide the possibility for refined blasting (Manoj and Suresh, 2016; Leng et al, 2021). Blair (1993) found that there is no difference between ideal delay time (no error) and electronic detonators blasting, which indicated that the error of the electronic detonators can be ignored when the electronic detonators are used to predict blasting vibration.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, with the popularization of electronic detonators initiation technology, more and more blasting projects have begun to use electronic detonators. The electronic detonators can be programmed to a delay increment of 1 ms or less which provide the possibility for refined blasting (Manoj and Suresh, 2016; Leng et al, 2021). Blair (1993) found that there is no difference between ideal delay time (no error) and electronic detonators blasting, which indicated that the error of the electronic detonators can be ignored when the electronic detonators are used to predict blasting vibration.…”
Section: Introductionmentioning
confidence: 99%